2018
DOI: 10.3390/met8020117
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ductile, Brittle, and Fatigue Fractures of Metals Using Optical Coherence Tomography

Abstract: Some forensic in situ investigations, such as those needed in transportation (for aviation, maritime, road, or rail accidents) or for parts working under harsh conditions (e.g., pipes or turbines) would benefit from a method/technique that distinguishes ductile from brittle fractures of metals-as material defects are one of the potential causes of incidents. Nowadays, the gold standard in material studies is represented by scanning electron microscopy (SEM). However, SEM instruments are large, expensive, time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Our studies approached the analysis of broken, ductile, fragile and fatigue surfaces of alloys (steel, cast iron, non-ferrous alloys) obtained both via SEM and OCT [7,8]. Following these analyses, we have demonstrated that OCT can replace SEM for the breakage surface analysis.…”
Section: Analysis Of Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies approached the analysis of broken, ductile, fragile and fatigue surfaces of alloys (steel, cast iron, non-ferrous alloys) obtained both via SEM and OCT [7,8]. Following these analyses, we have demonstrated that OCT can replace SEM for the breakage surface analysis.…”
Section: Analysis Of Fracturesmentioning
confidence: 99%
“…The latter aspect implies that it cannot be utilized to perform in situ assessments, as it is required for example in forensic investigations-for example in the case of plane, train, or car accidents, as well as of other incidents, such as blade ruptures of turbines or pipe ruptures. Given the above, we have proposed, for the first time to our knowledge, the use of an IR-based imaging method, Optical Coherence Tomography (OCT) [5,6], to replace SEM in such investigations [7,8]. A low coherence interferometry method, OCT systems have (much) lower costs (roughly by a factor of 20), it does not require trained operators, and it can be utilized in situ, as mobile systems have been constructed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering materials are classified in accordance to their deformation at fracture (i.e., brittle or ductile), to the form and appearance of fracture where ductile fracture produces less serious problems than brittle fracture under the same operating conditions, and to the crystallographic manner in which the fracture occurs (i.e., sliding, cleavage) (Hutiu et al, 2018). Among the various failure mechanisms introduced (Fan et al, 2017), investigating those associated with a brittle and ductile fracture in metallic alloys is important.…”
Section: Introductionmentioning
confidence: 99%
“…OCT is a biomedical imaging techniquebased on the principles of low coherence interferometry, that has been initially developed for ophthalmology, especially for studies of the retina and cornea [10][11][12][13]; it has further on expanded towards imaging the skin [14], as well as the oral cavity, for both hard and soft tissue [15][16][17][18][19]. While OCT is being utilized in an increasing area of such biomedical applications, it has also begun to be used extensively in Non-Destructive Testing (NDT) of materials, both refractive (for which cross sections/B-scans can be provided -a major advantage of OCT [2026]) and reflective (i.e., metallic, for which the topography of material surfaces can be obtained [27,28]). …”
Section: Introductionmentioning
confidence: 99%